British Society of Lifestyle Medicine: Founding Principles and Current Achievements. Issue 3 (May 2020) - Lawson, Rob
The British Society of Lifestyle Medicine in the United Kingdom was first established in 2016 partly in response to the 'sick man of Europe' tag applied to our nations due to the increasing prevalence of non-communicable diseases. Today it is contributing to the growing momentum and growing realisation that a new approach is vital for our Nations' health.